Balancing bytes and bliss: Sustaining happiness in a digital age - Harriet Burrow (BioScientist: The Salford Biomedicine Society Magazine, 2024)
In a growing digital age, it is not new information that technology is creating an “antisocial” generation. But have these technologies created platforms for positive change as well? In 2024, 98% of UK adults aged 16-24 now have a smartphone1. These can be amazing tools for networking, studying, and relaxing, however, the majority of time spent on these is spent watching TV and scrolling social media. In a Uswitch survey in 2022, the average person in the UK’s screen time is over 5 hours4. This is over 20% of their day spent looking at a screen. Overall, the time spent studying or relaxing is significantly lower than time spent online, this cannot be beneficial to a young adult’s mental or physical health. Moderate usage of these technologies has proved the most productive, due to its connectivity enhancement, financial inclusion, and access to information. In short, digital technology is a double-edged sword.